Innovation Of The Sipemang Application Using Qr Code For Monitoring And Preserving Mangrove Ecosystems In Pari City Village - Sri Wahyuni; Abdul Khaliq; Hanifah Mutia Zaida Ningrum Amrul; Aulia Akbar (Yayasan Sinergi Multidimensi Kreatif, 2024)
Mangrove ecosystems have an important role in maintaining the balance of the coastal environment. However, its existence is increasingly threatened by human activities and climate change. Effective monitoring and preservation of mangrove ecosystems is crucial. Kota Pari Village, with its mangrove potential, needs an innovative system to support these efforts. Therefore, this study aims to develop a QR Code-based Mangrove Monitoring Information System application